Perbandingan Metode IRR (Internal Rate of Return) dan Payback Period dalam Capital Budgeting pada PT. Pertamina (Persero) - Hana Maulida; Ratu Mutiara Juliyanti; Siti Wiwiarsih; Siti Nurfadia; Bambang Nur Indrawan; Mukhlishotul Jannah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study reviews the comparison between two popular methods in capital budgeting analysis, namely Internal Rate of Return (IRR) and Payback Period (PP), applied in the investment decision-making process at PT Pertamina (Persero). As a state-owned company in the energy sector that runs various important projects, Pertamina needs to evaluate investment feasibility efficiently. IRR is used to assess the effectiveness of long-term investments by taking into account all cash flows as well as the time value of money, while PP emphasizes more on how quickly the initial capital can be returned. This article uses a literature study method with a descriptive-qualitative approach to explore the advantages and disadvantages of each method. The results of the discussion show that IRR provides a more precise picture of long-term investment returns, while PP is useful for identifying projects that quickly return capital. Nonetheless, the use of each method alone is not comprehensive enough. Therefore, it is recommended that Pertamina integrate IRR and PP with other approaches such as Net Present Value (NPV) and sensitivity analysis to support more comprehensive and strategic investment decisions.